2015
DOI: 10.1111/gcb.12908
|View full text |Cite
|
Sign up to set email alerts
|

Lignin decomposition is sustained under fluctuating redox conditions in humid tropical forest soils

Abstract: Lignin mineralization represents a critical flux in the terrestrial carbon (C) cycle, yet little is known about mechanisms and environmental factors controlling lignin breakdown in mineral soils. Hypoxia is thought to suppress lignin decomposition, yet potential effects of oxygen (O ) variability in surface soils have not been explored. Here, we tested the impact of redox fluctuations on lignin breakdown in humid tropical forest soils during ten-week laboratory incubations. We used synthetic lignins labeled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 69 publications
(151 reference statements)
3
55
2
Order By: Relevance
“…Our previous work (Hall et al, 2015a) demonstrated that redox fluctuations increased the contribution of methoxyl groups in lignin to respiration from a tropical forest soil relative to static aerobic conditions. Here, we report an additional experiment where soils were amended with aqueous Fe(II) to simulate a highly reduced microsite, and then exposed to aerobic or fluctuating aerobic/hypoxic conditions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our previous work (Hall et al, 2015a) demonstrated that redox fluctuations increased the contribution of methoxyl groups in lignin to respiration from a tropical forest soil relative to static aerobic conditions. Here, we report an additional experiment where soils were amended with aqueous Fe(II) to simulate a highly reduced microsite, and then exposed to aerobic or fluctuating aerobic/hypoxic conditions.…”
Section: Introductionmentioning
confidence: 95%
“…Iron-lignin interactions in soils are also complicated by potential stimulation of decomposition by solid-phase and soluble Fe. Fenton reactions driven by coupled biotic/abiotic Fe redox cycling can decompose lignin (Yelle et al, 2011), and may be important in Ferich soils that experience fluctuating O 2 (Hall et al, 2015a;Hall and Silver, 2013). Also, Fe minerals such as goethite can abiotically oxidize SOM (Chorover and Amistadi, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin is the second most abundant natural polymer next to cellulose and hemicellulose and the most abundant aromatic polymer in terrestrial ecosystems, accounting for 15 to 30% by weights of dry biomass (Hall et al 2015;Klein et al 2015). As the global effort increases to find a high-valued biorefinery route, the importance of lignin quantity determination has proven to be paramount (Lupoi et al 2015).…”
Section: Introductionmentioning
confidence: 99%